Enhanced biological phosphorus removal by granular sludge in anaerobic/aerobic/anoxic SBR during start-up period. Issue 13 (15th March 2016) - Jiang, Xinxin; Yuan, Yixing; Ma, Fang; Tian, Jiayu; Wang, Yu
Abstract: Laboratory experiments were conducted to investigate the granulation process of the activated sludge in an anaerobic/aerobic/anoxic sequencing batch reactor (A/O/A SBR) during the start-up period. Under the condition of aeration intensity (6.5 L/min) and settling time (2 min), well-formed granular sludge was obtained in the A/O/A SBR, and the COD, phosphorus, and nitrogen removal efficiencies of the reactor for one typical cycle were as high as 90.1, 99.9, and 94.5%, respectively. Dynamics of microbial community in the reactor were monitored by polymerase chain reaction and denaturing gradient gel electrophoresis techniques. The results showed that microbial diversity of the granular sludge decreased compared with the initial sludge. However, strains which could assimilate excessive phosphorus became dominant in granular sludge, leading to the increase in the phosphorus removal efficiency of the reactor. Batch tests were conducted with three different electron acceptors, that is, oxygen, nitrate, and nitrite. It was observed that phosphorus removal efficiency of the reactor supplied with nitrite was only 43.4%, indicating that nitrite could be used as electron acceptor for phosphorus removal, but was less efficient than nitrate and oxygen.